Mimosa pudica l. juice for medical treatment / Fatin Azwa Ghazali …[et al.] - Ghazali, Fatin Azwa; Hamiruddin, Khairunnisa; Jailani, Norazura; Harun, Siti Hajar; Abd Razak, Nurin Jazlina (2019)
Mica juice Sdn Bhd located in No 31, Bangunan Arked Mara Jalan Rahmat 83000 Batu Pahat Johor Darul Takzim which enables to someone who has a health problem that they want and had to settle for with our service give. Mica juice Sdn Bhd also offers our service on any in terms of age differences. Mica juice Sdn Bhd also sold by health care product retail and we also capable of serving to whole family in a time and facilitate our service give. Population all over Malaysia decided to use our service when they had disease this are one way to improve their disease, for example this juice can prevent from asthma, diabetes, reduce urinary tract stones and others. Mica juice enterprise was predicted this opportunity to provide best quality and highest from solution to cure some diseases to all citizens, although age or their sex. Mica juice Sdn Bhd, see this business opportunities have potential success provided that it handled efficiently. People always needed to keep their hair health and care; users can feel more confident and comfortable. Mica juice Sdn Bhd see this as one way to succeed in this market, by cash in on from all needs of people, because this can improve healthy all users.